2004
DOI: 10.1158/1078-0432.ccr-04-0221
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Irinotecan

Abstract: Purpose:The purpose is to demonstrate whether an appropriately designed liposomal formulation of irinotecan is effective in treating mice with liver-localized colorectal carcinomas.Experimental Design: Irinotecan was encapsulated in 1,2-distearoyl-sn-glycero-3-phosphocholine/cholesterol (55:45 molar ratio) liposomes using an ionophore (A23187)-generated transmembrane proton gradient. This formulation was evaluated in vivo by measuring plasma elimination of liposomal lipid and drug after i.v. administration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…The liposomal lipid elimination rate was comparable to that described previously for DSPC/Chol liposomes. 31 These results suggest that Cu(DDC) 2 prepared inside DSPC/Chol liposomes does not remain inside the liposomes following iv dosing. This result was surprising given the stability of the formulation as determined using in vitro methods ( Figure 1).…”
mentioning
confidence: 87%
“…The liposomal lipid elimination rate was comparable to that described previously for DSPC/Chol liposomes. 31 These results suggest that Cu(DDC) 2 prepared inside DSPC/Chol liposomes does not remain inside the liposomes following iv dosing. This result was surprising given the stability of the formulation as determined using in vitro methods ( Figure 1).…”
mentioning
confidence: 87%
“…An orthotopic GBM pre-clinical study showed anti-vascular activity of doxorubicin when encapsulated in LNPs, and these effects were not observed with the free form of the drug or in normal brain tissue (Zhou et al, 2002). Other pre-clinical studies showed that liposomal formulations of irinotecan are more efficacious than the unencapsulated form in brain tumors (Krauze et al, 2007;Noble et al, 2006;Verreault et al, 2011b) and in colorectal and adenocarcinoma tumors (Hattori et al, 2009;Messerer et al, 2004;Ramsay et al, 2008). More specifically, our laboratory has established that Irinophore C TM (IrC TM ), a LPN formulation of irinotecan, exhibits improved anti-cancer efficacy compared to the free drug in a GBM orthotopic model (Verreault et al, 2011b).…”
Section: Lipid Nanoparticle Delivery Systemsmentioning
confidence: 98%
“…Despite these theoretical advantages, prior liposomal formulations of irinotecan, as well as of other camptothecins (lurtotecan and SN-38, among others), have not necessarily shown improved pharmacokinetic characteristics or toxicity profiles compared to their free drug counterparts when evaluated in the preclinical setting. [32][33][34] …”
Section: Introduction To Nal-iri: Initial Drug Developmentmentioning
confidence: 99%